1983
DOI: 10.1111/j.1399-3011.1983.tb02093.x
|View full text |Cite
|
Sign up to set email alerts
|

The toxic peptides from Amanita mushrooms

Abstract: The results of 50 years of effort in the chemistry of Amanita toxins are reviewed. The phallotoxins, fast acting components, but not responsible for fatal intoxications after ingestion, are bicyclic heptapeptides. They combine with F-actin, stabilizing this protein against several destabilizing influences. The virotoxins likewise fast acting are monocyclic heptapeptides. The amatoxins which are the real toxins lead to death within several days by inhibiting the enzymatic synthesis of m-RNA. They are bicyclic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 106 publications
0
64
0
3
Order By: Relevance
“…To demonstrate the requirement for RNA-and proteindependent mechanisms in the cardioprotection afforded by CP, we used AMN, an irreversible inhibitor of nuclear and mitochondrial RNA transcription that acts by binding to RNA polymerase II, and CHX, an irreversible protein synthesis inhibitor that halts mRNA translation by blocking the translocation of tRNA at the ribosome (16,18,45). Our results showed that the inhibition of RNA or protein synthesis decreases the cardioprotection provided by CP (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the requirement for RNA-and proteindependent mechanisms in the cardioprotection afforded by CP, we used AMN, an irreversible inhibitor of nuclear and mitochondrial RNA transcription that acts by binding to RNA polymerase II, and CHX, an irreversible protein synthesis inhibitor that halts mRNA translation by blocking the translocation of tRNA at the ribosome (16,18,45). Our results showed that the inhibition of RNA or protein synthesis decreases the cardioprotection provided by CP (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Control hearts (control ϩ AMN and control ϩ CHX) were then perfused for 155 min. CP hearts (CP ϩ AMN and CP ϩ CHX) received CP for 5 min before 30 min of GI and 120 min of reperfusion (16,18,45). Control hearts were preperfused for 55 min with Krebs-Ringer solution containing either AMN or CHX and then were perfused for 150 min with Krebs-Ringer solution alone (n ϭ 4 each).…”
mentioning
confidence: 99%
“…5 The pathological findings reflect the mechanism of action of amanitin, which binds to RNA polymerase II, inhibiting transcription of mRNA and leading to diminished protein synthesis and eventual cell death. 10,11 In reported cases, hepatocytes and renal proximal tubules are consistently affected, which may reflect high rates of protein synthesis in these cells. 4,6,7 Accordingly, serum chemistry values in cases of amanitin toxicosis reflect aberrations in hepatic, and often renal, function.…”
Section: Discussionmentioning
confidence: 99%
“…The cycle peptide chain, α-amanitin, has eight amino acids: asparagine, hydroxyl proline, dihydroxy isoleucine, hydroxyl-mercapto-tryptophan, glycine, isoleucine, glycine and alanine. Hydroxyl proline and dihydroxy isoleucine activate RNA polymerase II and III by binding to the enzyme molecule, enhancing the activating effect by means of glycine and isoleucine binding [6][7][8]. The immediate cause of death from mushroom poisoning is kidney, liver and respiratory failure which occur within one week of ingestion.…”
Section: Introductionmentioning
confidence: 99%